Hydro-Priming of Seed Improves the Water Use Efficiency, Grain Yield and Net Economic Return of Wheat under Different Moisture Regimes - Meena, Raj Pal; Sendhil, R; Tripathi, SC; Chander, Subhash; Chhokar, RS; Sharma, RK (SAARC Journal of Agriculture, 2014)
Wheat is the second most important staple food crop of India and contributes a major share to food basket of the country. Since majority of the area under wheat is irrigated, it consumes huge quantity of fresh water for its cultivation. The availability of good quality water for irrigation is decreasing over a period of time due to vagaries of monsoon, urbanization and industrialization. The biggest challenge on this front is to improve the efficiency and productivity of water being used in existing cropping system. Therefore, it is the need of hour to improve water use efficiency for wheat production. In the milieu, the present investigation was taken with an objective of studying the effect of pre-germinated seed in crop establishment under sub-optimal soil moisture conditions by using the residual soil moisture after harvesting of rice in Indo-Gangetic plains, so that pre sowing irrigation requirement for crop establishment may be cut and reduced in time period which require from pre-sowing irrigation to field preparation. This experiment was conducted for two consecutive years 2010-11 and 2011-12 to evaluate the influence of hydropriming on the water use efficiency and grain yield of wheat (Triticum aestivum L.) under moisture stress. The experiment was conducted in split plot design with three replications keeping moisture stress treatments (optimum moisture, sub-optimal moisture and dry soil followed by irrigation) in main plots and seed priming treatments (dry seed, hydropriming, and pre-germinated seeds) in subplots. Pregerminated seed produced significantly higher grain yield (5.49 t ha-1), which was statistically similar to hydropriming (5.30 t ha-1). Various seeding methods were statistically at par. The hydro-primed and pregerminated seeds established earlier than dry seeds leading to better crop establishment under optimum, sub optimum soil moisture as well as dry soil conditions leading to higher tillering and grain yield. The results of experiment showed that priming with plain water and pre-germinated seeds improved germination indices, seedling growth and crop establishment. Since priming with plain water and to have pregerminated seeds is simple and cheap method, which can increase germination percentage and homogeneity of seedling emergence under water stress conditions and it can be easily used by farmers. Interactive effect of different seed priming techniques along with seeding at sub optimal soil moisture level proved to be an efficient technique for enhancing water productivity of wheat crop. DOI: http://dx.doi.org/10.3329/sja.v11i2.18410 SAARC J. Agri., 11(2): 149-159 (2013)